Editorial (special issue on learner involvement) - Jo Mynard (Studies in Self-Access Learning Journal, 2011)
Learner involvement is relevant to self-access learning in a number of ways and this special issue will highlight three of them through its contributions. Firstly, there is a learner’s involvement in his or or her own self-directed learning. Secondly, there is the emotional involvement with learning. Thirdly, there is learner involvement in the actual running of a self-access centre.